Ukraińskie migrantki i migranci w aglomeracji warszawskiej: Cechy społeczno-demograficzne i relacje społeczne. Raport z badań - Agata Górny; Ewa Jaźwińska (University of Warsaw, Centre of Migration Research (CMR), 2019)
– The report presents selected results of the survey on Ukrainian migrants conducted in Warsaw and its vicinities in 2016. It describes histories of Ukrainian citizens' migration to Poland from the perspective of their professional and family situation and in relation to their social networks and social capital. It addresses differences between male and female migrants by demonstrating that, on the average, women have longer experience with migration to Poland and tend to start their migration at older age and more often as persons possessing already their own families (e.g. children) in Ukraine. By examining transitions of migrants' professional status, the report reveals barriers for socio-economic integration of migrants in Poland and points to differences in sectoral concentration of male and female Ukrainian workers. As it regards social networks of studied migrants, especially of women, what attracts attention is their homogeneity in relation to various individual characteristics of persons involved in these networks such as citizenship, education, wealth and age. Both for men and women resources achievable by means of these networks are first of all of practical (e.g. help in finding job or accommodation) and emotional character. Overall, the results of the described survey point to the high importance of the gender dimension in migration and everyday integration of Ukrainian migrants in Poland.
Keywords: 330; Ukrainian migrants; everyday integration; gender differences; professional status; social networks; social capital